Legal Review of Land Acquisition from Indigenous Peoples in the Nusantara Capital City (IKN) Project: Tinjauan Hukum Terhadap Pengadaan Tanah Masyarakat Adat Dalam Proyek Ibu Kota Nusantara (IKN) - Elrika Elrika; Benny Djaja (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The development of the new capital city, Ibu Kota Nusantara (IKN), as a National Strategic Project requires large-scale land acquisition, including areas traditionally occupied by Indigenous communities. Specific Background: Although legal frameworks such as the Basic Agrarian Law, the IKN Law, and Presidential Regulation No. 65/2022 formally acknowledge Indigenous land rights, their implementation remains inconsistent. Knowledge Gap: There is still no clear mechanism for verifying customary (ulayat) rights, determining culturally appropriate compensation, or ensuring meaningful participation of Indigenous communities in land acquisition processes. Aims: This study aims to examine the effectiveness of the existing legal framework governing land acquisition for IKN and assess the extent of protection afforded to Indigenous peoples. Results: The findings show that despite normative recognition of Indigenous rights, practical implementation faces barriers, including unclear procedures, limited community involvement, and compensation that fails to reflect the social, cultural, and spiritual value of customary land. Novelty: This research highlights the urgent need for specific legal instruments regulating the recognition and protection of ulayat rights within national strategic projects—an aspect largely absent in current regulations. Implications: Strengthening regulations, establishing holistic compensation standards, and ensuring inclusive participation and dispute-resolution mechanisms are essential to achieving a fair and sustainable land acquisition process for Indigenous communities affected by the IKN project. Highlights: The legal framework recognizes Indigenous land rights, but implementation remains inconsistent. Customary land holds cultural and spiritual value that is not reflected in current compensation models. Strengthened regulations and inclusive participation are essential for fair land acquisition in IKN. Keywords: Land Acquisition, Indigenous Peoples, Customary Rights, Ibu Kota Nusantara, Legal Protection